Evaluating Adoption Dynamics of Environment Friendly Practices (EFP) in Vegetable cultivation in Madhya Pradesh, India - Patel, Neerja; Chouhan, Sandeep; Singh, S. R. K. (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
The important eco-friendly technologies trustworthy of determining are organic farming, natural farming, traditional farming, green farming, bio-dynamic and pharma culture, which may be all together considered as eco-friendly farming. United States Department of Agriculture (USDA, 1980) has defined eco-farming (organic farming) as a production system, which prevents the use of synthetic fertilizers, pesticides, growth regulators and livestock feed additives. It preferably depends more upon crop rotation, crop residues, animal wastes, legumes, green manure, farm wastes, mechanical cultivation and biological pest management. The area under vegetable crops in Indore district of Madhya Pradesh was about 33.77 thousand hectares in 2010-11, which increased to 6.23 thousand hectares in 2011-12. The production of vegetable crops in Indore district was about 599307 metric tonne in 2010-11 and further increased to 29753 metric ton in 2011-12. (Horti.Dept, M.P.). This study was conducted in Indore district of Madhya Pradesh with the sample size of 120 respondents. A sample of 120 vegetable growers was drawn from 10 vegetable growing villages using proportionate random sampling technique. The findings revealed that use of pheroman trap (10.83%), use of light trap (12.5%), Conservation and encouraging of predators (0.83%), Use of NPV and concentration of spray (4.16%), Introduction of bio-control agents (10.00%), Preparation of seed kernel extract (5.83%), Knowledge about neem seed kernel extract (16.83%) vegetable growers adopt eco-friendly practices in vegetables cultivation.